Integrating Dimensions of Justice into Marital Property and Inheritance Rulings in Religious Courts - Rasyid Rizani; M Hafiah; Wahidah Wahidah (The Indonesian Journal of Islamic Law and Civil Law, 2026)
This research analyzes the integration of moral, legal, and social justice dimensions in rulings on marital property and inheritance cases in Indonesian Religious Courts. The study is motivated by the juridical dilemma faced by judges when reconciling normative legal certainty with dynamic substantive justice demands in contemporary Islamic society. This research explores the synergy between Western philosophy (Plato, Aristotle, Rawls) and Islamic philosophy (Al-Farabi, Al-Ghazali) to analyze harmony, proportionality, and social benefit. Using a layered theoretical framework ranging from legal protection to social engineering, this study employs a normative juridical method to examine judicial reasoning. The findings argue that the ijtihad performed by judges is essentially a method of legal discovery (rechtsvinding). This pattern of rechtsvinding demands interpretative flexibility, enabling judges to move beyond rigid statutory boundaries. By prioritizing substantive justice over formalistic norms, judges may employ contra legem decisions, ensuring that legal discovery functions as a responsive tool for social engineering and equity.The research concludes that judges function as both moral agents and social engineers responsible for harmonizing legal certainty with moral and social values. This harmonization is the essence of judicial ijtihad to realize a comprehensive and contextual Islamic legal justice in Indonesia